The Role of Self-Efficacy, Motivation, and Connectedness in Dropout Intention in a Sample of Italian College Students - Chiara Buizza; Herald Cela; Giulio Sbravati; Sara Bornatici; Giuseppe Rainieri; Alberto Ghilardi (MDPI AG, 2024)
Dropout is a critical concern in higher education, with a considerable number of students leaving within the first two years of university. Dropout affects students' well-being and their academic and career prospects, and institutions' retention and graduation rates. The aim of this study was to explore the mediating role of motivation and cognitive strategies for learning in the relationship among self-efficacy, connectedness, and university dropout intention. A total of 790 Italian college freshmen were involved in this study. The sample was recruited through a web survey consisting of the Academic Motivation Scale, Perceived School Self-Efficacy Scale, University Connectedness Scale, and Self-Regulated Knowledge Scale-University. The freshmen's intentions to drop out were assessed with five questions. The average age of the freshmen was 20.9 years, most of them were female, and were attending a degree program in the medical area. The results show that self-efficacy is the most important predictor of dropout intentions, followed by university connectedness. Self-regulated knowledge has an important role in predicting dropout intention by acting as a mediator between self-efficacy and motivation.This study underlines the importance of investing in training and orientation interventions in order to develop the skills to face the university path, increasing self-efficacy, motivation, and consequently students' well-being.